2017
DOI: 10.11114/jets.v5i6.2372
|View full text |Cite
|
Sign up to set email alerts
|

Psychological Unsafety in Schools: The Development and Validation of a Scale

Abstract: Work related psychological unsafety defined as the degree to which employee perceive the risky work environment that hinder them to behave comfortably or to speak up what they think without fear of its possible negative consequences. The importance of psychological unsafety has already been laid down for organizational viability and development, but the main problem is lack of instrument to measure psychological unsafety in schools. So the aim of this study is to develop valid and reliable instrument. We devel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…The views of the participants were noted and an initial group consisting of 42 items were created for the study. A review of literature and a study of a scale developed by researchers like Yildirim and Yenipinar (2017) led to the elimination of 15 of the items, and a pool of 27 items were used in a pilot study involving a sample of 43 high school students chosen by convenience sampling. The pilot study indicated that six of the chosen items had low factor loadings, and they were eliminated.…”
Section: The Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…The views of the participants were noted and an initial group consisting of 42 items were created for the study. A review of literature and a study of a scale developed by researchers like Yildirim and Yenipinar (2017) led to the elimination of 15 of the items, and a pool of 27 items were used in a pilot study involving a sample of 43 high school students chosen by convenience sampling. The pilot study indicated that six of the chosen items had low factor loadings, and they were eliminated.…”
Section: The Methodsmentioning
confidence: 99%
“…Yildirim and Yenipinar (2017) developed and validated a scale for psychological ‘unsafety’ in Turkish schools. The main study involved a sample of 393 school students.…”
Section: Review Of Literaturementioning
confidence: 99%
See 2 more Smart Citations